THE RELATIONSHIP BETWEEN FAST FOOD CONSUMPTION AND OBESITY IN WOMEN OF CHILDBEARING AGE IN BANDUNG - Salma Karisa; Agil Dhiemitra Aulia Dewi (Ikatan Sarjana Gizi Indonesia (ISAGI), 2022)
Obesity is one of the nutritional problems that occur in Indonesia where the prevalence continues to increase every year. The prevalence of obesity in Indonesia is higher in the female group compared to the male group. Obesity that occurs in women, especially in women of childbearing age can cause health problems such as irregular menstrual cycles, PCOS (Polycystic Ovary Syndrome) and even miscarriage in pregnancy. One of the factors that increase the risk of obesity is the frequency of consuming fast food. This study aims to determine the relationship between fast food consumption and obesity in women of childbearing age in Bandung. The type of research used in this study is cross sectional with research subjects are women aged 15-49 years. This research was conducted in Bandung with total 155 respondents as the sample. Analysis of the data was use chi square analysis. The results of this study indicate that there is a significant relationship between fast food consumption and the incidence of obesity in women of childbearing age in Bandung (P = 0.007). The conclusion of this study is that there is a relationship between the fast food consumption and the incidence of obesity in women of childbearing age in Bandung.